The Survival Strategy of Poor People in Surakarta - Dekasari, Dita Agnes; Zuber, Ahmad; Slamet, Yulius (KOMUNITAS: International Journal of Indonesian Society and Culture, 2018)
This research aimed to find out the surviving strategy of poor people in Kelurahan Semanggi, Pasar Kliwon Sub District, Surakarta. This study employed descriptive case study research method, with purposive sampling being the technique for selecting informant and poor people living in Kelurahan Semanggi, Pasar Kliwon Sub District, Surakarta being the unit of analysis to be studied. Data collection was conducted through in-depth interview, observation, and documentation of activities related to the surviving strategy of poor people in Kelurahan Semanggi, Pasar Kliwon Sub District, Surakarta. Data validation was carried out using data source triangulation with an interactive model of data analysis. The result of research showed that the surviving strategy taken by poor people in Kelurahan Semanggi was divided into 3. Firstly, active strategy was taken by telling the wife to work in order to help suffice the family’s need. Secondly, passive strategy was taken to apply parsimoniously living pattern, such as minimizing money spending, prioritizing more the expenditure for food need than that for other needs, minimizing the expenditure for their children’s pocket money and some people admitted that they were dependent on the government’s grant. Thirdly, the final strategy was network strategy taken by borrowing money from relatives, neighbor and other relations.